Anak dan Kekerasan Seksual: Tinjauan Yuridis terhadap Perlindungan Hukum dalam Sistem Hukum Indonesia: Children and Sexual Violence: A Legal Review of Legal Protection in the Indonesian Legal System - Manan, Najwa Septianingsih; Tanudjaja, Tanudjaja (Perspektif Hukum, 2025)
This study aims to examine the legal perspectives on the urgency of legal protection for child victims of sexual violence. It employs a normative juridical approach with a focus on legislation. The findings underscore the necessity of establishing rehabilitation for child victims of sexual violence as a legal obligation. First, the mental and physical conditions of victims are vulnerable and require rehabilitation. Second, there are significant weaknesses when rehabilitation is incorporated into the concept of restitution. Third, there are no legal provisions mandating rehabilitation for child victims of sexual violence; currently, only perpetrators are required to undergo rehabilitation as part of their punishment. Consequently, there is no clear and definitive regulation regarding the obligation of the state to provide rehabilitation for child victims of sexual violence.